Clinical phenotypes of IgG4-related disease reflect different prognostic outcomes. (27th June 2020) - Lanzillotta, Marco; Campochiaro, Corrado; Mancuso, Gaia; Ramirez, Giuseppe Alvise; Capurso, Gabriele; Falconi, Massimo; Dagna, Lorenzo; Della-Torre, Emanuel
Abstract: Introduction: Four clinical phenotypes of IgG4-related disease (IgG4-RD) have been recently identified by latent class analysis (LCA): pancreato-biliary (group 1); retroperitoneum/aortitis (group 2); head and neck limited (group 3); and Mikulicz/systemic (group 4). The reproducibility of this classification in clinical practice and its relevance for patient management, however, remain unknown. Methods: The study included 179 patients. Four IgG4-RD experts were asked to classify a validation cohort of 40 patients according to published LCA-derived phenotypes based on clinical judgement. Agreement between LCA and clinical clustering was calculated. To assess differences among disease phenotypes, the following variables were recorded on an additional 139 patients: serum IgG4 and IgE; inflammatory markers; eosinophils; plasmablasts; IgG4-RD responder index (RI); history of atopy, diabetes, osteoporosis, relapses and malignancy; cumulative dose of glucocorticoids; and use of rituximab. Results: Clinical judgement replicated LCA classification with strong agreement among IgG4-RD experts (κ = 0.841, P < 0.0005). At disease onset, group 1 showed the highest levels of serum IgG4 and IgE. Groups 2 and 4 had the lowest and highest IgG4-RD RI, respectively. At 2 years' follow-up, group 3 received the highest cumulative dose of glucocorticoids, but higher incidences of diabetes mellitus were observed in groups 1 and 4, consistent with the higher likelihood of pancreatic involvement in groups 1 and 4. No difference among the four groups was observed in terms of disease recurrence, time to relapse and frequency of rituximab infusion. Conclusion: Clinical phenotypes of IgG4-RD reflect differences in epidemiological features and prognostic outcomes.